PENERAPAN MODEL PEMBELAJARAN JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMPN 1 KARANGPLOSO - Dwi Ambar Amargawati (Center of Language and Cultural Studies, 2017)
This study aims to determine the increase of mathematics learning outcomes through the implementation of jigsaw learning model in class VII. The design of this study was classroom action research conducted in two cycles. Results of the study showed student learning activities in the cycles increased by 13.46%, teacher activity 7.36%, and students’ learning outomes up to 95%. Minimum mastery was accomplished by 30 (95%) students and only 2 students that reached below minimum mastery, and average score 78,45.